Penolakan Parsial Kritikus terhadap Rawi Shaduq: Telaah Kritis atas ar-Rabi bin Anas - Adam, Faisal; Ahmadi, Husni; Arifin, Tajul (Darul Yasin Al Sys, 2024)
Al-Jarh wat Ta’dil is an important field in hadith studies that provides information about the conditions of hadith narrators based on critiques by critical scholars. These critiques follow a hierarchical structure, with shaduq being a level two endorsement after tsiqat. Despite being an endorsement, a narration from a shaduq narrator is not accepted outright and requires further scrutiny. This research analyzes the acceptance status of narrations from shaduq narrators according to critical scholars. It critically examines the case of the shaduq narrator named ar-Rabi bin Anas and investigates the reception status of his narrations. The methodology employed is qualitative with a descriptive-analytical approach, using references such as al-Jarh wat-Ta’dil literature, mustalah hadith, hadith collections, relevant books, and journals. The study demonstrates that among shaduq narrators, some receive negative critiques leading to partial rejection of their narrations. Furthermore, it shows that narrations from shaduq like ar-Rabi bin Anas are rejected if: First, they have negative critiques from scholars supported by indications after comparison with parallel narrations. Second, their hadiths are transmitted by problematic disciples; in ar-Rabi's case, his problematic disciple is Abu Ja’far ar-Razi, and the narration by this disciple occurs in isolation.